Risk factors of tumor lysis syndrome in childhood acute lymphoblastic leukemia - Andarsini, Mia Ratwita; Hartono, Audylia; Cahyadi, Andi; Larasati, Maria Christina Shanty; Asmara, Almeir Pradhipta Andras (Universa Medicina, 2024)
BackgroundAcute lymphoblastic leukemia (ALL) is the most common childhood hematologic malignancy. Treatment failure in ALL can be caused by severe and life-threatening complications, including tumor lysis syndrome (TLS). Delay in identifying risk factors and establishing the diagnosis of TLS by clinicians can be fatal. This study aimed to determine the risk factors for TLS in children with ALL. MethodsThis was a retrospective cross-sectional study on 81 children aged 0 to 18 years with ALL. Tumor lysis syndrome comes in two forms: laboratory and clinical. Laboratory TLS occurs if uric acid levels >normal values, potassium >6mEq/L, phosphate >6.5mg/dl, and calcium <7mg/dl. Clinical TLS includes an increase in serum creatinine, the presence of heart attacks, sudden death, and seizures. Risk factors for TLS include age, nutritional status, leukocyte count, presence of organ infiltration, presence of mediastinal mass, uric acid level, renal function, and type of chemotherapy regimen. Risk factors were analyzed using simple and multiple logistic regression analyses. A value of p<0.05 indicates a significant risk factor. ResultsTwenty seven patients (33.3%) experienced TLS. Adjusted OR analysis showed that the presence of organ infiltration (aOR 5.42; 95% CI 1.45-20.27; p=0.012), leukocyte count (aOR 8.70; 95% CI 1.67-45.13; p=0.010), and decreased kidney function (aOR 12.21; 95% CI 1.09-136.89; p=0.042) were significant risk factors for TLS. ConclusionDecreased renal function, leukocyte count, and organ infiltration were significant risk factors for TLS. We suggest more vigilant assessment and monitoring to recognize and treat those patients who are at risk of TLS.